Optical measurement of microvascular oxygenation and blood flow responses in awake mouse cortex during functional activation. Issue 3 (March 2022) - Şencan, İkbal and Esipova, Tatiana and Kılıç, Kıvılcım and Li, Baoqiang and Desjardins, Michèle and Yaseen, Mohammad A and Wang, Hui and Porter, Jason E and Kura, Sreekanth and Fu, Buyin and Secomb, Timothy W and Boas, David A and Vinogradov, Sergei A and Devor, Anna and Sakadžić, Sava
The cerebral cortex has a number of conserved morphological and functional characteristics across brain regions and species. Among them, the laminar differences in microvascular density and mitochondrial cytochrome c oxidase staining suggest potential laminar variability in the baseline O2 metabolism and/or laminar variability in both O2 demand and hemodynamic response. Here, we investigate the laminar profile of stimulus-induced intravascular partial pressure of O2 (pO2) transients to stimulus-induced neuronal activation in fully awake mice using two-photon phosphorescence lifetime microscopy. Our results demonstrate that stimulus-induced changes in intravascular pO2 are conserved across cortical layers I–IV, suggesting a tightly controlled neurovascular response to provide adequate O2 supply across cortical depth. In addition, we observed a larger change in venular O2 saturation (ΔsO2 ) compared to arterioles, a gradual increase in venular ΔsO2 response towards the cortical surface, and absence of the intravascular "initial dip" previously reported under anesthesia. This study paves the way for quantification of layer-specific cerebral O2 metabolic responses, facilitating investigation of brain energetics in health and disease and informed interpretation of laminar blood oxygen level dependent functional magnetic resonance imaging signals.